Effects of Remission and Genetic Variation on Brain Structure in Treatment-Resistant Major Depressive Disorder: A Prospective, Longitudinal Imaging Study - Phillips, Jennifer (Université d'Ottawa / University of Ottawa, 2015)
Previous magnetic resonance imaging (MRI) studies have demonstrated brain atrophy in major depressive disorder (MDD) that is progressive with continuing illness and may be reversible with antidepressant treatment. What remains unclear is whether brain structure can be positively affected by pharmacological intervention even if patients fail to remit on the treatment. The primary aim of this thesis was to prospectively track changes in brain structure in patients with treatment-resistant depression while they underwent pharmacotherapy with the goal of attaining remission. There is evidence that gene variants associated with poorer antidepressant response also confer greater risk of volume reduction in the hippocampus. A secondary aim of the thesis was to investigate the effects of monoaminergic-related gene variants on hippocampal volume in patients and controls at baseline imaging. Outpatients with treatment-resistant MDD underwent structural MRI scans at baseline and after either 6-months of sustained remission or 12-months of failure to remit. Matched controls were scanned once to provide comparison data for patients’ baseline scans. Participants also provided blood samples for genetic analyses. Imaging outcome measures included longitudinal changes in whole-brain volume, and gray matter volume and mean cortical thickness within specific cortico-limbic regions of interest (ROIs). Over follow-up, remitted patients had an increase in whole-brain volume, while nonremitted patients lost brain volume despite receiving more treatment strategies. Remitters and nonremitters also showed subtle changes in volume and thickness over time in several ROIs in opposing directions, with increasing hippocampal volume and cortical thickness in the rostral middle frontal gyrus and orbitofrontal cortex in remitters, and decreasing volume or thickness in these regions in nonremitters. Genetic imaging analyses revealed that polymorphisms in certain norepinephrine- and serotonin-related genes have similar effects on hippocampal volume in patients and controls, while the serotonin transporter polymorphism differentially affects hippocampal volume in the presence of depression. Given the observations of volume increase in remitted patients and continuing atrophy in nonremitters, pharmacotherapy in the absence of sustained remission is likely insufficient to elicit structural recovery in depression. This finding is important since the restoration of brain structure in patients with treatment-resistant depression may have positive implications for their future prognosis.
Keywords: Major Depressive Disorder; Magnetic Resonance Imaging; Hippocampus; Brain Volume; Treatment Resistance; Genetics; Remission